Well-Posedness of the Ocean-Atmosphere Coupled Model (CSIAM Transactions on Applied Mathematics, 2025)
In this work, we consider the dynamic framework of the ocean-atmosphere(O-A) coupled model with physical boundary conditions at the ocean-atmosphereinterface, and this coupled model can be viewed as atmosphere general circulationmodel coupled with ocean general circulation model. As the initial data and boundaryconditions are assumed to meet certain assumptions, by taking advantage of energyestimates method and compactness arguments, we addressed the existence and stability of global weak solutions, the existence and uniqueness of global strong solution tothe O-A coupled model.